Perbandingan Kekuatan Fleksural Antara Orientasi Unidirectional dan Bidirectional Fiber Agave Sisalana pada Fiber Reinforced Composite - Erfandi Ahmad; Purwanto Agustiono; Dyah Irnawati (Jurnal Material Kedokteran Gigi, 2014)
Fiber reinforced composite (FRC) contains a polimer matrix and fibers. The FRC application as a dental splinting material requires a considerable fleksural strength to withstand the mastication forces. The fiber orientation is one factor influences the mechanical strength of FRC. The aim of study was to compare the fleksural strength between unidirectional and bidirectional orientations of sisal fiber (Agave sisalana) on FRC. The FRC with a flowable composite matrix (Master Flow, Brazil) and sisal fiber (Agave sisalana) (Balittas, Indonesia) were used. The FRC samples (25x2x2mm) were made with unidirectional and bidirectional fibers orientation (n=4). The fleksural strengths were measured using the universal testing machine and the data were analyzed statistically using an independent t-test (a=0,05). The results showed that the average fleksural strength of FRC unidirectional group was 36.56 ± 2.91 MPa and bidirectional group was 24.09 ± 2.08 MPa. The independent t-test showed a significant difference in fleksural strength between unidirectional orientation and bidirectional orientation fiber (p <0.05). This study reveals that the fleksural strength of FRC with unidirectional orientation was greater than the bidirectional orientation of sisal fiber (Agave sisalana).